ENHANCING SCIENCE LEARNING OUTCOMES THROUGH HUMAN RESPIRATORY ORGAN PUZZLE MEDIA AMONG FIFTH-GRADE STUDENTS AT SD NEGERI LAMREUNG, ACEH BESAR - Helminsyah Helminsyah; Tria Marvida (Jurnal Visipena, 2023)
This study aims to determine the effect of using Human Respiratory Organ Puzzle Media on improving science learning outcomes of fifth-grade students at SD Negeri Lamreung, Aceh Besar. The media was designed to help students understand respiratory organ concepts through enjoyable and contextual interaction. This research employed a quantitative approach with a quasi-experimental Pretest-Posttest Control Group Design, involving 40 students (20 control, 20 experimental). Data were collected through learning outcome tests and student response questionnaires, analyzed using t-tests. Validity test results showed all items were valid (r-count > r-table) and the instruments were reliable (Cronbach's Alpha > 0.60). Normality tests showed data were normally distributed (Sig. > 0.05). Paired Sample t-test results showed a significant difference between experimental and control classes with Sig. (2-tailed) = 0.000 < 0.05 and t = -15.515. These findings indicate that the Human Respiratory Organ Puzzle Media significantly improves learning outcomes, motivation, cooperation, and active engagement of students in elementary school science learning.